Toleransi Model Salafi - Maimanah; Nor’ainah; Husnul Khatimah (Interdisciplinary Explorations in Research Journal, 2024)
Abstract As a multicultural area, South Kalimantan is inhabited by various followers of various religions, ethnicities and cultures. Likewise, various religious sects of mass organizations and various religious communities exist in South Kalimantan. In such a context, contact between religions, between communities and between organizations and others is common. This is where it is important for one party to understand the other to be tolerant of each other, so that the conducive atmosphere in South Kalimantan is maintained. Salafi as a reform movement that is relatively new with its mission of purifying Islam, of course, has had a lot of contact with other Islamic movements such as NU, Muhammadiyah, Jamaah Tabligh and others. In this case, it is important to understand the Salafis further, especially in the context of tolerance. According to Salafis, the ideal tolerance is tolerance as practiced by the Prophet and and salafus shaleh. How the concept of Salafi tolerance will be discussed further in this paper. Keywords: Salafi, tolerance, concept   Abstrak Sebagai sebuah daerah yang multikultural, Kalimantan Selatan ditempati oleh berbagai pemeluk agama, suku dan budaya  yang beragam. Demikian juga berbagai aliran keagamaan organisasi massa dan berbagai komunitas keagamaan ada di Kalimantan Selatan. Dalam konteks yang demikian, persentuhan antaragama, antar komunitas dan antar organisasi dan lain-lain lumrah terjadi. Di sinilah pentingnya satu pihak memahami pihak yang lain untuk kemudian saling bertoleransi, agar suasana kondusif di Kalimantan Selatan terus terpelihara. Salafi sebagai salah satu gerakan pembaharuan yang relatif baru dengan misi pemurnian Islamnya, tentu banyak mengalami persentuhan dengan gerakan-gerakan Islam lainnya seperti NU, Muhammadiyah, Jamaah Tabligh dan lain-lain juga terjadi. Dalam hal ini penting untuk memahami Salafi lebih jauh terutama dalam konteks toleransinya. Menurut Salafi   toleransi yang ideal  adalah toleransi sebagaimana yang dipraktikkan oleh Nabi saw dan para sahabat serta para salafus shaleh. Bagaimana konsep toleransi Salafi tersebut akan dibahas lebih jauh dalam makalah ini. Kata Kunci: Salafi, toleransi, konsep